PENGARUH PEMBERIAN TABLET FE DENGAN JUS JAMBU BIJI TERHADAP PERUBAHAN KADAR HEMOGLOBIN IBU HAMIL ANEMIA DI PUSKESMAS PEMBANTU PULAU PALAS KECAMATAN TEMBILAHAN HULU - Mia Rita Sari (Jurnal Kesehatan Husada Gemilang, 2018)
In 2013, the anemia prevalence of pregnant women in Indonesia was 37, 1%. Giving 90 Fe tablets to pregnant women at Tembilahan Hulu Health Center in 2016 was 57%, and at Auxiliary Health Center of Pulau Palas was 19%. This research aims at identifying the influence of giving of Fe tables with the guava juice towards the changes of hemoglobin levels in anemic pregnant women at the Auxiliary Health Center of Pulau Palas Tembilahan Hulu. This research is analytical quasi-experimental descriptive with non-randomized pretest and posttest with control group design. The population of the research is all pregnant women at the Auxiliary Health Center of Pulau Palas in 2016 (120 people), with a sample of 32 respondents and each group consists of 16 respondents. The sample was taken by accidental sampling. Data analysis was done by using Dependent T test. The results of the experimental group revealed the HB average of pregnant women before being given the Fe tablets with guava juice was 9,438 and after administration was 11,462 with a difference in the HB average of pregnant women after being given the Fe tablets with guava juice was 2,024 and p value 0,000. However, in the control group the HB average of pregnant women before being given Fe tablets was 9.825 and after administration was 9.775 with a difference in the average HB of pregnant women after being given Fe tablets was 0.05 with p value 0.765. It is recommended to health workers, the provision of KIE in normal pregnant women in general and especially in anemic pregnant women is to give KIE (consuming Fe tablets). Fe tablets can be consumed using guava juice which aims to maximize absorption so that the high risk of pregnant women can be prevented from the beginning of their pregnancy.